Connecting the young and the young at heart: an intergenerational music program: Program Profile. Issue 3 (3rd July 2018) - David, Justin; Yeung, Michelle; Vu, John; Got, Tiffany; Mackinnon, Chelsea
ABSTRACT: Due to its universal appeal, music can bridge intergenerational gaps and improve overall quality of life. Many intergenerational programs have thus increasingly incorporated music into their design; however, the Hamilton Intergenerational Music Program (HIMP) is unique in that it focuses on general music participation as opposed to singing-only programming. Three elementary schools and long-term care homes were contacted and matched based on proximity to one another. Program facilitators ran four successive weeks of intergenerational music sessions. Activities included training the children how to interact with elderly participants, facilitating conversation with icebreakers, and performing music together. Qualitative feedback was gathered after each visit and comprised of observations from program facilitators and participants. Several benefits were observed following program visits such as the reduction of age-related stereotypes, improved participant morale, enhanced cognitive function, and development of meaningful relationships. While leaving the sessions, children recall positive interactions with the seniors, lament that their time together ended too quickly, and express excitement for the next session. The older adults articulate similar sentiments and ask children to return soon. With the countless lessons learned from the current program, much can be drawn to inform future expansion and implementation to other communities.